The Dynamics of Education Policy Implementation: Insights from USAID's Experience in Kenya - Mtembei, M'masi Sylvia (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2025)
This article explores the intricacies of implementing education policies in Kenya, specifically examining the contributions and obstacles faced by the United States Agency for International Development (USAID). This study evaluates the efficacy of USAID's initiatives in the education sector of Kenya, examining the intricacies of cooperation between governmental entities, non-governmental organizations (NGOs), and civil society groups. The study utilizes a quantitative research methodology and gathers data through a survey delivered to 120 respondents, who were selected to represent government, NGO, and civil society groups. The data is analyzed using descriptive statistics. The study highlights significant barriers such as insufficient government backing and restricted resources, while also emphasizing fruitful partnerships with non-governmental organizations (NGOs) and civil society. The research findings emphasize the crucial role of USAID in improving access to education and emphasize the need for more research to address gaps in policy relevance and implementation effectiveness. This paper provides useful insights into the discussion on international development and education reform, presenting proposals for enhancing policy implementation frameworks in Kenya and similar settings.